1996
DOI: 10.1016/s0022-5347(01)65403-x
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Synthase and Xanthine Oxidase Activities in the Spermatic Vein of Patients with Varicocele: A Potential Role for Nitric Oxide and Peroxynitrite in Sperm Dysfunction

Abstract: Our data suggest a high oxidative stress due to the release of nitric oxide synthase and xanthine oxidase within the dilated spermatic vein. The reaction resulted in dramatic formation of nitric oxide, peroxynitrite and S-nitrosothiols, which are biologically active. Formation of peroxynitrite from the reaction of nitric oxide with superoxide could be a causative factor for impaired sperm function in patients with varicocele.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 33 publications
3
57
0
Order By: Relevance
“…53 These patients have increased ROS in serum, testes, and semen samples. 54 Increased NO has also been demonstrated in the spermatic veins of patients with varicocele, 55,56 which could lead to spermatozoal dysfunction. 57 Varicocelectomy has been shown to increase the concentrations of antioxidants such as superoxide dismutase, catalase, glutathione peroxidase, and vitamin C in seminal plasma and improve the sperm quality.…”
Section: Varicocele and Osmentioning
confidence: 99%
“…53 These patients have increased ROS in serum, testes, and semen samples. 54 Increased NO has also been demonstrated in the spermatic veins of patients with varicocele, 55,56 which could lead to spermatozoal dysfunction. 57 Varicocelectomy has been shown to increase the concentrations of antioxidants such as superoxide dismutase, catalase, glutathione peroxidase, and vitamin C in seminal plasma and improve the sperm quality.…”
Section: Varicocele and Osmentioning
confidence: 99%
“…Thus, one clinically important issue regarding varicocele is preoperative recognition of who will respond to surgical treatment. Several studies have shown that ROS production is enhanced in varicocele patients [6,7], and that oxidative stress is present in spermatic vein blood and seminal plasma [8][9][10]. Oxidative stress results from an imbalance between the production and reduction of ROS.…”
Section: Discussionmentioning
confidence: 99%
“…In varicocele patients, ROS production is enhanced [6,7], and oxidative stress is present in spermatic vein blood and seminal plasma [8][9][10]. Varicocele treatment can significantly improve sperm parameters, by decreasing ROS concentration and increasing antioxidant capacity, and these effects lead to improved sperm parameters finally [11].…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, enhanced free radical generation by the spermatozoa and/or precursor germ cells has been repeatedly suggested, 65,72,73 on the other, there is evidence to suggest that excess free radical generation may involve the spermatic vein itself. 74 The excess generation of free radicals by the spermatozoa may be an indirect consequence of impaired spermatogenesis/epididymal function resulting in the retention of excess residual cytoplasm. The presence of excess cytoplasm has been positively correlated with the generation of ROS by human spermatozoa, via mechanisms involving the facilitated supply NADPH to oxidases in the sperm plasma membrane.…”
Section: Disruption Of the Antioxidant Status Of The Testesmentioning
confidence: 99%